PRODUCTIVITY IMPROVEMENT LAPPING POT PADA MESIN AUTO CONTOUR LAPPING - Novebriantika; Agung Handi Wibowo; Nurul Fadilah; Rahman Hakim; Yusuf Nurhuda; Ita Wijayanti (Jurnal Teknologi Dan Riset Terapan (JATRA), 2025)
Improving seal production output requires productivity enhancements that increase the efficiency and effectiveness of both machinery and tooling. One of the main issues was identified in the auto contour lapping machine, particularly in the lapping pot, which was considered ineffective and inefficient in its application. This condition resulted in low production output, longer processing times, and increased material waste due to the use of rubber-based lapping pots. To overcome these limitations, an improved lapping pot was designed and manufactured using 3D printing technology, replacing rubber with filament material to reduce production waste. This study focuses on the design, fabrication, and feasibility evaluation of the improved lapping pot through direct implementation in the production process. Performance evaluation included visual inspection, free height measurement, and surface quality inspection of the seals. The results show that the improved lapping pot is suitable for production use and significantly enhances productivity. By accommodating four seals in a single lapping pot, the processing time was reduced by a total of 75 seconds per cycle. Consequently, production output increased fourfold from 144 seals per hour to 576 seals per hour, while the seal quality remained consistent and met customer-required dimensions and specifications.